2000
DOI: 10.1088/0953-8984/12/6/312
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic properties of proton transfer in hydrogen-bonded molecular systems

Abstract: The mechanism of the formation of ionic and bonding defects and the interaction between protons and heavy ions in hydrogen-bonded molecular systems is investigated and a new model is constructed. This model considers two coupled sublattices corresponding to those of protons and heavy ions in order to study the dynamic properties resulting from deformation and local fluctuation of the heavy ion sublattice due to the protonic displacements. As compared with other models, the model emphasizes, in particular, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…He thought that the peaks of 3540 cm −1 and 3665 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds without hydrogen bonds in free water; the 3280 cm −1 and 3415 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds with hydrogen bonds in linear hydrogen-bonded chains and are a result of the red-shift of frequency of the former, respectively, due to the occurrence of linear chains; the 3017 cm −1 and 3165 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds in the closed hydrogen-bonded chains and are a result of the red-shift of frequency of 3282 cm −1 and 3416 cm −1 , respectively, due to the forms of closed chains [15,16,19] . Based on the molecular structure of water Pang further established the theory of magnetization of water according to the theories of proton conductivity in the hydrogen bonded systems of ice [17][18][19][20][21][22] and magnetism of matter. If water is exposed in a magnetic field, these closed hydrogen-bonded chains become some ring electric-current or "molecular electric-current" elements with magnetism due to the proton conductivity in them under the action of Lorentz force of the magnetic field [19][20][21][22][23][24]25] , thus the magnetic interactions of these "molecular electric-current" elements with each other or with the externally applied magnetic-field result in the changes of distribution and features of water molecules and the magnetization of water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He thought that the peaks of 3540 cm −1 and 3665 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds without hydrogen bonds in free water; the 3280 cm −1 and 3415 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds with hydrogen bonds in linear hydrogen-bonded chains and are a result of the red-shift of frequency of the former, respectively, due to the occurrence of linear chains; the 3017 cm −1 and 3165 cm −1 should attribute to the symmetric and antisymmetric stretching-vibrations of OH bonds in the closed hydrogen-bonded chains and are a result of the red-shift of frequency of 3282 cm −1 and 3416 cm −1 , respectively, due to the forms of closed chains [15,16,19] . Based on the molecular structure of water Pang further established the theory of magnetization of water according to the theories of proton conductivity in the hydrogen bonded systems of ice [17][18][19][20][21][22] and magnetism of matter. If water is exposed in a magnetic field, these closed hydrogen-bonded chains become some ring electric-current or "molecular electric-current" elements with magnetism due to the proton conductivity in them under the action of Lorentz force of the magnetic field [19][20][21][22][23][24]25] , thus the magnetic interactions of these "molecular electric-current" elements with each other or with the externally applied magnetic-field result in the changes of distribution and features of water molecules and the magnetization of water.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the molecular structure of water Pang further established the theory of magnetization of water according to the theories of proton conductivity in the hydrogen bonded systems of ice [17][18][19][20][21][22] and magnetism of matter. If water is exposed in a magnetic field, these closed hydrogen-bonded chains become some ring electric-current or "molecular electric-current" elements with magnetism due to the proton conductivity in them under the action of Lorentz force of the magnetic field [19][20][21][22][23][24]25] , thus the magnetic interactions of these "molecular electric-current" elements with each other or with the externally applied magnetic-field result in the changes of distribution and features of water molecules and the magnetization of water. The above experimental results, for example, the occurrences of six peaks in different ranges of temperatures and magnetic fields, saturation effect, memory effect, the irreversible process in the changing process of water temperature, the exponential increase of ultraviolet absorption and magnetism effect of magnetized water, support and convince the real existence of clustering structure of hydrogen-bonded chains of molecules and magnetic interactions among these clustering structures of molecules in them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is out of question that quantum fluctuations and thermal perturbations are expected to cause the Davydov soliton to decay into a delocalized state. Some numerical simulations indicated that the Davydov soliton is not stable at the biological temperature of 300 K [62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]. Other simulations indicated that the Davydov soliton was stable at 300 K [30][31][32][33][34][35][36][37][38][39], but they were based on the classical equations of motion which were likely to yield unreliable estimates of the stability of the soliton [13][14][15][16][17][18].…”
Section: Review Articlementioning
confidence: 99%
“…(21) the following can be obtained [46,47,[62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78][79][80]:…”
Section: Equations Of Moton and The Soliton Solutionmentioning
confidence: 99%